Implementasi Customer Relationship Management Berbasis Web Pada Toko Baizuri Bunut - Ersa Rezekia Putri (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Engaged in sales, Baizuri Bunut Store provides all personal needs, such as shoes, wallets and belts. The ordering process made by customers in ordering a product is still manual, namely by visiting the Baizuri Store directly. Another problem is the lack of facilities that help customers to get information about products, and interact with the store to submit suggestions and criticisms. As well as experiencing difficulties in the process of managing and storing customer data that has made transactions. In the services provided by the Baizuri Bunut Store, it is also still not effective, thereby reducing the level of effectiveness of competition in the business, the demand for products is increasing day by day, which can trigger the Baizuri Bunut Store to be able to compete in providing quality products and increase competitive advantage. This can be achieved by managing the flow of information, the flow of the sales system, between suppliers, companies and distributors using Customer Relationship Management. By using qualitative methods with interviews or direct observation, aims to describe the facts of a situation at the research site. The purpose of this research is to provide information about products such as shoes, wallets and belts produced by the Baizuri Bunut Store in an updated manner and to be able to promote their business and business at a low cost but have extraordinary effectiveness and increase the efficiency of product information processing management.